Investigate on dissimilar welding of high-entropy alloy and 310S with various fillers - Chihhsien Liao; Tingen Shen; Weichen Hsu; Hsiencheng Wu; Chenchou Chung; Chunlung Peng; Chewei Tsai (Materials & Design)
This study investigates the microstructure and mechanical properties of non-equimolar CoCrFeMoNi high-entropy alloy (HEA) and SUS310S stainless steel dissimilar welds using different filler materials. The dissimilar welding was performed on gas tungsten arc welding with Inconel 82, Inconel 625, and 316L stainless steel fillers. The non-equimolar CoCrFeMoNi HEA is shown effective weldability with these fillers, maintaining distinguished phase stability and structural integrity. Microstructural analysis revealed varied grain morphologies influenced by the heat in the fusion zone and heat-affected zone. Mechanical properties were evaluated through tensile and hardness tests, showing that welds with Inconel 625 filler exhibited superior strength and ductility. The weld hardness value was maintained at 170 HV, with a yield strength of 301 MPa and an ultimate tensile strength of 587 MPa, resulting in a joint efficiency of 106 %.